2013
DOI: 10.1186/1471-2334-13-7
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypovitaminosis D correlates with increased inflammatory markers in HIV infected patients

Abstract: BackgroundEven though it has been suggested that antiretroviral therapy has an impact on severe hypovitaminosis D (SHD) in HIV infected patients, it could be speculated that the different levels of residual inflammation on HAART (Highly Active Anti Retroviral Therapy) could contribute to SHD and aggravate bone catabolism in these patients.MethodsA cross-sectional study was carried out in an unselected cohort of 263 HIV infected outpatients consulting during Spring 2010. Clinical examinations were performed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 21 publications
2
34
1
Order By: Relevance
“…The prevalence of hypovitaminosis D was 24% and that of vitamin D deficiency was 1.6%, a result that was considered lower than in other studies of HIV-infected patients (12,19,25,26,29). Although prevalence was not high, it should be emphasized that Maceió is a city located at a low latitude, with high UV index (30), and high sunlight incidence all year long.…”
Section: Resultsmentioning
confidence: 46%
See 2 more Smart Citations
“…The prevalence of hypovitaminosis D was 24% and that of vitamin D deficiency was 1.6%, a result that was considered lower than in other studies of HIV-infected patients (12,19,25,26,29). Although prevalence was not high, it should be emphasized that Maceió is a city located at a low latitude, with high UV index (30), and high sunlight incidence all year long.…”
Section: Resultsmentioning
confidence: 46%
“…In this study, there was no association between alcohol intake and/or smoking with hypovitaminosis D. As for smoking, some studies with HIV carriers (19,25,26) showed a significant association with hypovitaminosis D, while other did not (12,29).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…33 The association with 25(OH)D and TNF-a has not been reported from other studies of HIV-infected cohorts; however, in a randomized study of HIV-uninfected adults with congestive heart failure, TNF-a was stable over 9 months in the vitamin D repletion group but increased by 12% in the placebo group ( p = 0.017) suggesting a protective benefit in the inflammatory milieu of heart failure. 34 While at least one cross-sectional study has shown no association between low 25(OH)D levels and systemic inflammation, 22 several other cross-sectional studies have shown associations with IL-6 and hs-CRP [11][12][13] as well as with soluble TNF receptor 1 (sTNFR1), 35 soluble TNF receptor 2 (sTNFR2), and resistin. 13 These studies have included adults both on and off ART and most did not require virologic suppression for study inclusion, making direct comparisons with our cohort difficult.…”
Section: Vitamin D Insufficiency and Inflammation In Chronic Hiv Infementioning
confidence: 99%
“…10 Vitamin D levels may also have important implications for inflammation in patients with HIV infection. An emerging body of data in this population suggests associations between low vitamin D levels and elevated markers of inflammation including interleukin-6 (IL-6) and highsensitivity C-reactive protein (hs-CRP), [11][12][13] and in a random sample of 1,985 HIV-infected individuals in Europe, higher vitamin D levels were independently associated with a lower risk of mortality and AIDS events after adjusting for ART use, CD4…”
mentioning
confidence: 99%